Wykorzystanie eye trackingu do analizy wizualnych informacji statystycznych - Szalach, Adam; Osińska, Veslava; Jankowska, Adela (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The correct interpretation of statistical data presented using visualization methods is a challenge in relation to modern media and communication. This is mainly due to poorly designed charts and often intentional manipulation of data presented graphically. Another problem may be the limited time that the recipients have at their disposal to familiarize themselves with the visualizations, e.g. via television. The task is additionally more difficult when the presented information concerns socially important matters. Users’ perception of such specific visual information can be tested using a currently proven eye-tracking method. The following article will present the results of a pilot study conducted on a group of 13 respondents. Developed and thematically diversified surveys presented to the respondents were intended to help determine how the recipients read the charts, how long it takes them to read the data correctly, and whether the respondents are able to locate any errors. The experiment was carried out using the eye-tracking technique supported by the survey method.